PENGEMBANGAN MANAJEMEN PENDIDIKAN MADRASAH (Studi tentang Pengembangan Manajemen dan Pengajaran di MA NU Demak) - Kasdi, Abdurrahman (QUALITY, 2013)
Nowadays people need a quality education, especially the schools that give a balance loads between religious and general education.This is because the parents’ awareness of the importance ofreligious education for their children was increasing, in order tocounteract the negative effects exhaled by globalization, especially the moral decadence and rampant cases of drugs among young people. It is a challenge and opportunity for Islamic institutions,especially the Islamic high school (Madrasah Aliyah), which beganto rise to become an excellent school. Here are four things thathave to be met by madrasah to be a leading educational institution:first, the implementation of curriculum strategies. Second, thedevelopment of management based on madrasah. Third, create asynergistic relationship between teachers and students. Fourth, thereorientation of the teaching system. The official recognition of theinstitution of madrasah as a subsystem of national education is its challenge to show that madrasah is one of competitive educational institutions that is acceptable to all people, especially to those whoare not familiar with madrasah. This study will attempt to explorethe strategy of Madrasah Aliyah Nahdlatul Ulama Demak in theimplementation of curriculum to fulfill that expectation during academic year 2012/2013.